Trajetória tecnológica ambiental: o caso da tecnologia de reuso de água do Pólo Petroquímico do ABC - Pallerosi, Guilherme Guimaraes (Universidade Federal de São Carlos, 2010)
We propose a reflection on the technological progress of the twentieth century and the significance of environmental technologies for the new millennium. The object of analysis are the hydrics resoucers capitation techniques from the petrochemical industry of São Paulo. The metropolitan region of São Paulo is one of most populous areas of the country and with high pluviometric level. In the end of the twentieth century, several factors made the hydrics resources a fundamental point for the productive system in this region, pressing for changes in water capitation technologies. The environmental technology of water reuse can be considered the unique technique really innovative between the others found during the field work. Even with the obvious advantages, a complex negociation appears necessary for making new technological paradigms. The modern development, occurred throughout the twentieth century, brought technological advances that deeply influenced the society ways of life and environment, causing the saturation of the current development model. The society patterns of production and consumption began to be questioned from the emergence of social values of environmental preservation. In this context, the environmental technologies have become an important object of study, both for economics and for the social sciences, contributing to undertanding of new technological paradigms.
Keywords: Desenvolvimento social - ciência, tecnologia e sociedade; Tecnologia - aspectos sociais; Sociologia ambiental; Novas tecnologias - impacto social; CIENCIAS SOCIAIS APLICADAS